Islamic perspective on importance of breastfeeding: Two case reports - Mokhtar, Nurhawa; Sulaiman, Fatin Syuhadah; Kusumawardani, Anisa; Hasan, Taufiq Hidayat (2016)
Introduction: Breast milk contains all basic nutrition needed by a child. Exclusive breastfeeding is recommended to all infants in their first 6 months of life. Infants who had been exclusively breastfed have a better health status compared to infants who was introduced with mixed feeding in their early life. Exclusive breastfeeding not only give benefit to the child, but also the mother. In infants, it confers protective mechanism in lowering risk of gastrointestinal infection and promotes bonding between the mother and the child. Case Report: The first case is a 2 years and 7 months old girl who was admitted to Hospital Tengku Ampuan Afzan Kuantan due to acute gastroenteritis with some dehydration. She was also admitted one month ago due to pneumonia. She was breast fed exclusively only for 3 months old due to working mother. The mother started formula feeding since then. The second case is a 1 year and 4 months old boy who was hospitalized due to acute bronchiolitis. He was not breast fed due to no milk production. Discussions: Islam views childhood as a critical phase in molding an individual. Parents have been entrusted by Allah to observe and fulfill the rights of the children in providing a conducive environment for children to develop. A good healthcare and proper nutrition are among the child’s rights that need to be fulfilled by the parents. Islam emphasizes the importance of breastfeeding up to 2 years old as a way in providing good nutrition. Islam also provides solution for mothers who are unable to breastfed their child by adopting wet mother. Conclusions: Parents are responsible in providing good health and nutrition to their children. Breastfeeding not only highly encouraged by Islam but also provides medical benefits for both mother and children.